Iterations of Silence - Pintér, Leila (Hungarian Journal of English and American Studies, 2022)
Book review: Fadem, Maureen E. Ruprecht. Silence and Articulacy in the Poetry of Medbh McGuckian. Lanham: Lexington Books, 2019. 310 pages. ISBN 978-1-7936-0707-2. E-book. 115.